The analytical method versus the traditional method of teaching the electrical theory of direct current motors in Dunwoody institute - Drinkall, Leon R., author; Hinderman, Roy Aaron, 1900-, advisor; Newkirk, Louis V., committee member; Wetzel, Clarence Ludwig, committee member; Beaty, Fred B., committee member; Betts, Gilbert L., committee member; Avery, George T., committee member (Colorado State University. Libraries, 1941)
To view the abstract, please see the full text of the document.
Keywords: Electric motors, Direct current; Electrical engineering -- Study and teaching